All my friends are ghosts - Vidaurri, S. M. (KaBoom!, 2020)
Effie feels like a ghost and that she doesn't belong. After a particularly horrible day, she runs away into the strange woods by her school and discovers a school for ghosts. As Effie learns about all the things ghosts can do, she and her new friends track down a lost soul and try to free it. But it will take more than ghostly powers-- Effie will have to look deep inside herself and trust in her new friends.